2018
DOI: 10.1186/s12916-017-0999-x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal dysbiosis increases risk of preterm fetal membrane rupture, neonatal sepsis and is exacerbated by erythromycin

Abstract: BackgroundPreterm prelabour rupture of the fetal membranes (PPROM) precedes 30% of preterm births and is a risk factor for early onset neonatal sepsis. As PPROM is strongly associated with ascending vaginal infection, prophylactic antibiotics are widely used. The evolution of vaginal microbiota compositions associated with PPROM and the impact of antibiotics on bacterial compositions are unknown.MethodsWe prospectively assessed vaginal microbiota prior to and following PPROM using MiSeq-based sequencing of 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
218
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(237 citation statements)
references
References 83 publications
4
218
0
15
Order By: Relevance
“…Ehsanipoor and colleagues propose that this bimodal distribution is due to the underlying aetiology of cervical dilation and that there may be two subsets of women, those destined for favourable outcomes following cerclage and those likely to deliver early because of subclinical infection . We, and others, have demonstrated associations between the bacterial community structure of the vaginal microbiome, and the risk and outcome of spontaneous preterm labour and PPROM . We have also shown that cervical cerclage is effective in preventing PTB in women with mechanical damage to their cervix caused by ablative treatment for cervical intraepithelial neoplasia .…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Ehsanipoor and colleagues propose that this bimodal distribution is due to the underlying aetiology of cervical dilation and that there may be two subsets of women, those destined for favourable outcomes following cerclage and those likely to deliver early because of subclinical infection . We, and others, have demonstrated associations between the bacterial community structure of the vaginal microbiome, and the risk and outcome of spontaneous preterm labour and PPROM . We have also shown that cervical cerclage is effective in preventing PTB in women with mechanical damage to their cervix caused by ablative treatment for cervical intraepithelial neoplasia .…”
Section: Discussionmentioning
confidence: 52%
“…We, and others, have demonstrated associations between the bacterial community structure of the vaginal microbiome, and the risk and outcome of spontaneous preterm labour and PPROM . We have also shown that cervical cerclage is effective in preventing PTB in women with mechanical damage to their cervix caused by ablative treatment for cervical intraepithelial neoplasia . We therefore hypothesised that women presenting with silent cervical dilation represent at least two aetiological groups.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…There were no differences between groups in the rates of hypertensive disorders and smoking habits. However, these lower rates of small-for-gestational-age new-borns found could be related to the lower rates of urinary tract infections, which have been associated with higher risk of small-for-gestational-age new-borns [30,31] and prematurity [32]. The MedDiet enhanced with EVOO and nuts could have had a direct influence on the lower incidence of urinary tract infections.…”
Section: Discussionmentioning
confidence: 89%